Variation and sources of sterols in Kuala Selangor, Selangor - Masni Mohd Ali,; Norfariza Humrawali,; Mohd Talib Latif, (Universiti Kebangsaan Malaysia, 2010)
This study explores the role of sterols as lipid biomarkers to assess organic matter variations and their sources in surface sediments of Kuala Selangor, Selangor which involved extraction procedures and sterol compounds analyzed using GC-MS. Ten sterol compounds were found in the samples with phytosterol being the principal compounds which accounted 79% of total sterols. This was followed by cholesterol and fecal sterols, each constitutes 6% of total sterols while the rest are in the ranged of 1-5%. Sterol Source Index (SSI) also reflected phytosterols predominant at all sampling stations but in different degree based on phytosterol compounds. Another issue was sewage contamination assessment using coprostanol/cholesterol, coprostanol/(coprostanol+cholestanol) and epicoprostanol/coprostanol ratio. No sewage contamination occured in the study area even though fecal sterols have been quantified. This analytical study indicates that the sediments in the study area consisted of a mixture of sterols from various sources even though dominated by phytosterols originated from terrestrial plants.